Bone health in cyclists: Discrepancies between the axial and peripheral skeletons - Ducher, G.; Naughton, G. A.; Lorenzen, C. (Medicine & Science in Sports & Exercise, 2009)
Response of the authors to an article of Wilks et al. [Wilks, D.C.; Gilliver, S.F. & Rittweger, J. (2009). Forearm and tibial bone measures of distance- and sprint-trained master cyclists. Med. Sci. Sports Exerc., 41(3), 566-573, and answer of the authors to the response.